ANTI-INFLAMMATORY ACTIVITY OF WILD AND CULTIVATED VARIETIES OF ERANDA (RICINUS COMMUNIS LINN.) ROOT - A Doshi Krunal,; Rabinarayan, Acharya; Ravishankar, B; Nariya Mukesh, B (International Journal of Ayurveda and Pharma Research, 2015)
In Ayurveda, Eranda (Ricinus communis Linn; Euphorbiaceae) root is highlighted for its anti-inflammatory and analgesic action and used as one of the ingredient in many compound formulations. Ricinus communis L. is available both in wild as well as cultivated state. Due to its high demand and less supply of wild variety root, its cultivated variety is fulfilling the market demand. Hence, the present study is carried to evaluate the anti-inflammatory activity of both the varieties of Eranda root. Decoction of both wild and cultivated varieties of Eranda root (10.8 ml/kg) were taken as test drugs, Phenyl butazone (100 mg/kg) as reference standard and experiment was carried out on Wistar strain albino rats following carrageenan induced paw edema model. Students unpaired t test was applied for analyzing the obtained data, after one, three and five hours. Wild variety root decoction, at studied dose (10.8 ml/kg) level, showed marked decrease in paw edema, in comparison to normal control rats, after one hour (25.25%) and five hours (27.79%) of carrageenan injection. The wild variety root provides additional anti-inflammatory effect, in comparison to reference standard (in percentage form), after one hour (13.63%) and five hours (22.18%) whereas the cultivated variety decreased the inflammation after one hour (15.15%) and increase the inflammation after five hours (02.50%). Decoction of wild variety, of Ricinus communis L. root provided considerable suppression of carrageenan induced paw edema compared to its cultivated variety.